2003
DOI: 10.1038/sj.ijo.0802276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on HDL and LDL particle sizes in carriers of the null P207L or defective D9N mutation in the lipoprotein lipase gene: the Québec LipD Study

Abstract: BACKGROUND:We have recently demonstrated that French Canadians bearing a mutation in the lipoprotein lipase (LPL) gene present an impaired lipoprotein-lipid profile characterized by small low-density lipoprotein (LDL) and high-density lipoprotein (HDL) particles compared with healthy subjects. It has also been documented that obesity has a significant impact on HDL and LDL particle sizes. OBJECTIVE: To examine the extent to which obesity modulates HDL and LDL particle sizes among carriers of mutations in the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
3
11
0
1
Order By: Relevance
“…It was also observed that abnormal serum HDL occurred more in underweight subjects, contrary to the report documented in another study that showed an association between abnormal HDL and obesity. [30] Serum HDL predicted obesity in this study. Perhaps, our study subjects might have other morbidities that could account for this contrast, as they were patients presenting in the out-patient clinic.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…It was also observed that abnormal serum HDL occurred more in underweight subjects, contrary to the report documented in another study that showed an association between abnormal HDL and obesity. [30] Serum HDL predicted obesity in this study. Perhaps, our study subjects might have other morbidities that could account for this contrast, as they were patients presenting in the out-patient clinic.…”
Section: Discussionsupporting
confidence: 48%
“…This is in agreement with reports that have shown an association between obesity and LDL hypercholesterolemia. [29,30] Serum LDL is the major determinant of serum total cholesterol, and therefore increases as serum total cholesterol increases. [30] The association between BMI and serum HDL was significant, (df=3, p<0.001), as found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoprotein lipase merupakan enzim yang berperan penting dalam hidrolisis lemak. Kelainan pada enzim ini akan mengakibatkan peningkatan TG, LDL, VLDL, dan penurunan HDL (Ruel et al, 2003).…”
Section: Pembahasanunclassified
“…4,5 The phospholipase (PLA 2 ) family comprises a group of enzymes that hydrolyze the sn-2 ester bond in the glyceroacyl phospholipids present in lipoproteins and cell membranes. 6 Group IIA (-IIA) sPLA 2 is an acute-phase protein for which plasma levels were reported to correlate with that of C-reactive protein (CRP) and to be an independent risk factor and predictor of coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%